Variance from published guidelines and changes in temporal trends in the management of cutaneous malignant melanoma: a 5-year update. Issue 5 (17th August 2022) - Brownstone, Nicholas; Marson, Justin W.; Zakria, Danny; Farberg, Aaron; Rigel, Darrell
Abstract : This study aimed to assess the current management of melanoma from relative to present guidelines and determine changes 5 years ago. An eight-question survey was sent to practicing US dermatologists using the same methodology and questions from our JAAD study. Overall, saucerization/scoop biopsy (48%) was the most commonly used method. The most commonly chosen margin for melanoma in-situ (MMIS) removal was 6–10 mm (51% of respondents). For CMM with a depth greater than 1 mm, the most commonly chosen margins were in the 1.1–1.9 cm range (55% of respondents). More respondents referred cases of MMIS and CMM out for treatment as compared to 2016. Academic dermatologists in 2021 were 8% less likely to treat MMIS as compared to all other practice types in 2021, whereas 7% more likely to treat CMM greater than 1 mm. Academic dermatologists in 2016, as compared to 2021, were 4% more likely to treat MMIS and 19% more likely to treat CMM greater than 1 mm. A total of 91% of respondents reported having some change in their management of CMM. Our study findings suggest that a knowledge gap still exists representing a continued educational opportunity to more effectively distribute and implement CMM management guidelines.